DOMAIN NAME SYSTEM USING LINUX SERVER - Yanti Kumala; Jalinas Jalinas, SKom, MM (Jurnal Sistem Komputer, 2001)
The Internet is a set of many interconnected networks, that means exchanginginformation. On the internet network needed a system called DNS (Domain NameSystem) for easy use by network users to map IP-Address to the computer name(host). Without control, network users will simply find it difficult to know the addressto which computers communicate. In writing this control is only made with the Linuxoperating system.Computer network is a single computer model that serves all computing tasks anorganization has been replaced by a collection of numerous computers separate butinterrelated in performing their duties. Network architecture consisting of the OSIreference model and TCP / IP.In 1984, Paul Mockapetris created the control, ie domain-based naming pattern.Creating a database to control (Record) begins with the filling member domain. Zoneconsists of networks that are controlled by a single administrator. In making DNSBIND version 8 is used. BIND (Berkeley Internet Name Domain) is software forimplementing control. Making control starts with setting the required files, then yournext step is to activate it by running the program and the commands you want.Control not only be created by using Linux. However, it can also use siste4m otheroperations such as Novell Netware, Windows NT and OS / 2. If control has beencreated and activate it, then the next stage is to conduct testing on the network.